The Efficiency of Providing Animal Protein from Fish as Supplementary Feeding for Toddlers with Stunting - Nugroho, Muhammad Ridho; Yansyah, Dedi; Rhedo, Umarsyah; Armeidi, Erwin; Erawani, Feri Herita (CV Media Inti Teknologi, 2023)
Given its many benefits over other animal products as a source of protein, salmon is a very suitable source of animal protein to help initiatives that aim to enhance community nutrition and combat stunting. To keep Indonesia from losing its golden generation in the future, stunting must be treated appropriately. The aim of this study was to evaluate the impact of supplemental fish-based diet on the nutritional status of stunting toddlers. The sample in this study consisted of 26 stunted toddlers receiving fish-based supplementary feeding (PMT) for 90 days from September to December 2023 at the Simpang Periuk Health Center work area. An experimental design with a pre- and post-test strategy without control was used in this study's methodology. By contrasting the nutritional status of toddlers before and after the intervention, a paired sample test was utilized as the statistical analysis. December 2022 saw the completion of this study. The findings indicated that there were significant differences in the nutritional status of toddlers before and after receiving the intervention, with a p-value of 0.000 (.05) indicating that this was the case. It can therefore be deduced that providing fish-based PMT interventions for 90 days can improve toddlers' nutritional status, lowering the rate of stunting in the target toddlers.